Coupled Deterministic and Stochastic Modeling of an Industrial Multi‐Zone LDPE Autoclave Reactor. Issue 1 (February 2016) - Eckes, David; Busch, Markus
Summary: Simulation aided product design of LDPE often requires deep understanding of polymer architectures produced in the industrial polymerization. Therefore, a hybrid‐stochastic approach is further developed that allows for the good description of the typical polymeric microstructure produced in a multi‐zone autoclave reactor. The here presented kinetic network goes beyond the basic polymerization scheme and accounts for the propagation of terminal double bonds as well as the mechanical degradation of polymer molecules due to shear stress. By including these reactions a good agreement between experimental and predicted molecular weight distribution is achieved. Furthermore, the comparison of individual contraction factors from experimental data and contraction factors calculated by a 3‐D random walker result in a good agreement.